A study on the stereochemistry of direct conversion of polyamides to hydroxyesters using monomeric secondary chiral amines as a model compound. (February 2019) - Kamimura, Akio; Ikeda, Kosuke; Akinari, Yugo; Matsumoto, Hiroshi; Kaiso, Kouji
Abstract: Stereochemistry of direct conversion of polyamides to hydroxyesters was investigated using model compounds. Optically active secondary-alkyl amines underwent the conversion to corresponding secondary alcohols in moderate yields by treatment with supercritical methanol in the presence of glycolic acid. The reaction progressed through almost completely stereochemical inversion to give secondary alcohols in high yields. Thus, the substitution reaction of the amino group to hydroxyl group progresses through SN 2 type transition state accompanying with stereoinversion. Highlights: Primary and secondary alkyl amines were used as model compounds to investigate depolymerization mechanism of polyamides. The reaction pathway depends on the alkyl group and primary alkyl amine prefers substitution process to elimination process. Chiral secondary alkyl amines undergo complete stereoinversion, indicating the substitution goes through SN2 mechanism.